Processing the Chinese Reflexive “ziji”: Effects of Featural Constraints on Anaphor Resolution - He, Xiao; Kaiser, Elsi (Frontiers in Psychology, 2016)
We present three self-paced reading experiments that investigate the reflexive ziji ‘self’ in Chinese – in particular, we tested whether and how person-feature-based blocking guides comprehenders’ real-time processing and final interpretation of ziji. Prior work claims that in Chinese sentences like “John thought that {I/you/Bill} did not like ZIJI”, (i) the reflexive ziji can refer to the matrix subject John if the intervening subject is also a third person entity (e.g. Bill), but that (ii) an intervening first or second person pronoun blocks reference to the matrix subject, causing ziji to refer to the first or second person pronoun. However, native speakers’ judgments regarding the accessibility of long-distance antecedents are rather unstable, and researchers also disagree on what the exact configurations are that allow blocking. In addition, many open questions persist regarding the real-time processing of reflexives more generally, in particular regarding the accessibility (or lack thereof) of structurally unlicensed antecedents. We conducted three self-paced reading studies where we recorded people’s word-by-word reading times and also asked questions that probed their off-line interpretation of the reflexive ziji. People’s answers to the off-line questions show that blocking is not absolute: Comprehenders do allow significant numbers of non-local choices in both the first and the second person blocking conditions, albeit in small numbers. At the same time, the reading time data, particularly those from Experiments 2 and 3, show that comprehenders use person feature cues to quickly filter out inaccessible long-distance referents. The difference between on-line and off-line patterns points to the possibility that the interpretation of ziji unfolds over time: it seems that initially, during real-time processing, person-feature cues weigh more heavily and constrain what antecedent candidates get considered, but that at some later point, other kinds of information are also integrated and perhaps outweigh the person-feature constraint, resulting in consideration of referents that were initially ‘blocked’ due to the person-feature constraint. In sum, in addition to the structural constraints identified in prior work, person-featural cues also play a key role in regulating the on-line processing of reflexives in Chinese.